SCIENCE AND SCHOOL: APPROACHES TO EDUCATION - Mickūnas, Algis (Acta Paedagogica Vilnensia, 2009)
The article discusses the use of scientific theories for student and teacher development. Based on hermeneutic and phenomenologic traditions there are those approaches to personal development and teaching analized which provide and promote the development of the potential of the student. Firstly, it is shown how the intersubjective consiousness helps in perceiving and reflecting the things which are being experienced by a person and from the subjectivity leads to the intersubjective perception of the essence of things. The presented examples of legal facts analysis illustrate how in the process of development both the teacher and the student have “to learn” and perceive the essence and this way “acquire” the consiousness able to understand things not dependent on personal wishes and environment. The perception of essences is timeless, though the historic context is important for teaching / education. Hermeneutic analysis helps to relate the differences expressed by individual and communal, depending on tradition, understanding. It is presented how in the process of education a person might be liberated and empowered, but at the same time his / her powers are interrelated with those of the Other. It is important to acknowledge that in the process of personal liberation and personal powers development one cannot trespass the borders and hurt the powers of the Other, for culturally it is thanks to the Other that a person can develop and be empowered.